Tingkat Islamic Financial Literacy dan Penggunaan Fintech Terhadap Financial Inclusion UMKM Kawasan Pondok Pesantren di Kota Jombang - Lik - Anah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
The UMKM in Islamic Boarding School area continue to experience an increase in financial transactions in line with the increase in banking financial services, especially Islamic banking financial services, for example: BPRS, Syariah Bank, BMT and Micro Waqf Banks which are located around the area. The purpose of this study is to find out the level of Islamic financial literacy and the use of Fintech of UMKM in the Islamic boarding school area in Jombang. This is based on the data that the number of research is included in associative research with purposive sampling technique of all UMKM which are located in the Islamic boarding school area in Jombang, with the criteria of UMKM which have used Fintech services and banking services as the requirement in the area of financial inclusion. The method used in this research is multiple linear regression analysis which is strengthened by qualitative analysis to find out the quality of financial inclusion. The results showed that Islamic financial literacy has a positive and significant effect on financial inclusion. The use of Fintech has a positive and significant effect on UMKM financial inclusion. Islamic financial literacy and the use of Fintech have a positive and significant effect on the financial inclusion of UMKM in the Islamic boarding school area in Jombang city.